Violência psicológica contra adolescentes e Transtorno de Estresse Pós-traumático no Adolescente. - ÁLVARES, Livia Goreth Galvão Serejo (2019)
Introduction: Psychological violence is a form of abuse that names verbal or gestural aggressions in order to terrorize, reject, humiliate the victim, and isolate them from social interaction. It is considered as a risk for the development of mental disorders, among them the Post Traumatic Stress Disorder. However, there is still a gap on this form of violence, in isolation, especially in the adolescent population. Objective: To analyze the occurrence of psychological violence against adolescents in a cohort associated with the development of Posttraumatic Stress Disorder. Methods: A cross-sectional study using data from a cohort, followed up in 2016. With a sample of 2,515 adolescents (18/19 years old) who answered the self-administered questionnaire, where individual, family, social and presence aspects were addressed stressors, in addition to the instrument validated for the occurrence of psychological violence. Hierarchical modeling was used to analyze the factors associated with psychological violence in three blocks (socioeconomic and demographic factors, family and adolescent structural factors, as well as behavioral factors). The Directed Acyclic Graph was used to construct the theoretical model, control of confounding factors and selection of adjustment variables. In order to obtain the homogeneity of the comparison groups in relation to the variables, the Propensity Score was used as a method for causal inference, estimated by binary logistic regression with the likelihood method. Results: ARTICLE 1: Female adolescents suffered more severe psychological violence (OR: 1.38, 95% CI: 1.12-1.71). Possessing work, alcohol and illicit drug use, and insecurity in the place where he / she lives were associated with both forms of psychological violence (moderate and severe). ARTICLE 2: The prevalence of severe psychological violence was 30.3%. Severe violence was associated with Posttraumatic Stress Disorder in both analyzes, but the magnitude in the model structured by the Propensity Score (OR: 1.97; 95% CI: 1.08-3.56) indicated adjustment of the association measure of the crude analysis (OR: 3.40; 95% CI: 2.03-5.69). Conclusion: The occurrence of psychological violence among adolescents was high. In their most severe form, women ntering the labor market with unhealthy living habits are the main victims. Severe psychological violence is an important factor associated with the development of Posttraumatic Stress Disorder.